Chalk in earthworks and foundations proceedings of the symposium held at the Institution of Civil Engineers Thursday, 22nd April 1965. (Institution of Civil Engineers, 1966)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a symposium held in April 1965.